FAITH-BASED FOOD RESILIENCE: A FRAMING ANALYSIS OF ‘AISYIYAH’S PUBLIC DISCOURSE IN THE 108TH MILAD - Kholifatul Fauziah (Yayasan Nusantara Hasana Berdikari, 2025)
This study examines the framing of faith-based food resilience in ‘Aisyiyah's 108th Milad Address, a crucial public discourse from a prominent Indonesian faith-based women's organization. Employing a qualitative research approach and utilizing Robert Entman's framing model, the study systematically analyzes the speech to answer two core questions: how ‘Aisyiyah's discourse frames the problem and causes of faith-based food resilience, and how it frames the solutions and moral judgments related to these community development initiatives. Findings reveal that ‘Aisyiyah frames the problem beyond scarcity, critically highlighting food waste and attributing its causes to educational and moral deficiencies. Solutions are rooted in the holistic concept of